Survival rate of diabetic-related lower extremity amputees in hospitals in the Eastern Cape - Aviwe S. Mgibantaka; Alfred Musekiwa; Moleen Zunza (African Journal of Disability)
Background: Diabetes mellitus (DM) is a global health concern that has greatly affected South Africa. The gap in the current management of DM has resulted in complications such as lower extremity amputations (LEAs) and death. Eastern Cape province reflects this struggle, with disparities in access to healthcare and poor health outcomes. Understanding survival rates and associated factors between the urban Livingstone Hospital and the rural Nelson Mandela Academic Hospital can improve health interventions and outcomes.